2019
DOI: 10.1186/s12873-019-0257-y
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and weaknesses of the acute care systems in the United Kingdom and the Netherlands: what can we learn from each other?

Abstract: Background The demand on Emergency Departments and acute medical services is increasing internationally, creating pressure on health systems and negatively influencing the quality of delivered care. Visible consequences of the increased demand on acute services is crowding and queuing. This manifests as delays in the Emergency Departments, adverse clinical outcomes and poor patient experience. Overview Despite the similarities in the UK’s and Dutch health care systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…Given UK occupancy pressures, fi rstly reducing delays within acute control seems sensible, while continuing to work closely with social and community services (these are more complex to address and have major impact on costs 34 and LOS 16,17 . While undertaking a DoCS program, it is necessary to understand the healthcare system being surveyed, for example here in the UK 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Given UK occupancy pressures, fi rstly reducing delays within acute control seems sensible, while continuing to work closely with social and community services (these are more complex to address and have major impact on costs 34 and LOS 16,17 . While undertaking a DoCS program, it is necessary to understand the healthcare system being surveyed, for example here in the UK 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing international demand for acute medical services and diagnostic rate or intervention trends in the PED may explain the need for non-LA PED services. 6 8 14 36–38 …”
Section: Discussionmentioning
confidence: 99%
“…1–5 It would be expected that the recent global movement towards expansion of health insurance coverage would result in improved access to primary care or preventative services, thus reducing hospital ED visits. However, other studies have suggested the opposite may occur, 6–10 where the expansion and comprehensiveness of health insurance coverage may, on the other hand, increase the utilisation of hospital ED. 11–14 Due to the pervasive phenomenon of moral hazard in health insurance, whether comprehensive health insurance coverage may exacerbate potentially unnecessary ED utilisation has become a critical policy concern.…”
Section: Introductionmentioning
confidence: 97%
“…These include time constraints and clinically unwell patients. 8 We identified low use of CHA2DS2VASC and HAS-BLED scores in patients presenting with AF ( acute or paroxysmal). This might reflect inadequate prescription of oral anticoagulants to indicated patients.…”
Section: Introductionmentioning
confidence: 90%